2017
DOI: 10.21475/ajcs.17.11.12.pne808
|View full text |Cite
|
Sign up to set email alerts
|

Steady shallow water table did not decrease leaf expansion rate, specific leaf weight, and specific leaf water content in tomato plants

Abstract: It was presumed that shallow water table restricted leaf growth and some water-related parameters; therefore, they can be used as indicators of plant stress due to the water table condition. Objective of this research was to evaluate morphological stress indicators in tomato plants exposed to shallow water table. The research was conducted in two stages: (1) developing reliable LA estimation model from June to September 2016; as pre-requisite for (2) calculating and evaluating the morphological indicators for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 15 publications
0
15
0
2
Order By: Relevance
“…Based on results of these two experiments, it is fair to assume that critical depth of water table for common bean plant is between 10 and 13.5 cm. Nonetheless, Meihana et al (2017) reported that shallow water table was less harmful if the water table was at steady position. Under field condition, however, soil water table is more likely to fluctuate.…”
Section: Discussionmentioning
confidence: 99%
“…Based on results of these two experiments, it is fair to assume that critical depth of water table for common bean plant is between 10 and 13.5 cm. Nonetheless, Meihana et al (2017) reported that shallow water table was less harmful if the water table was at steady position. Under field condition, however, soil water table is more likely to fluctuate.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf area (LA) was estimated using state the estimation of the regression model. Specific leaf area (SLA), total leaf area (TLA), leaf area ratio (LAR) and relative leaf water content (RLWC) were calculated based on measured primary growth parameters (Meihana et al, 2017). Dry weight (DW) was measured after the leaves were exposed to 70 o C for 48 h and turgid weight (TW) was measured after rehydration for about 3 h untill a constant weight was reached.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the BWCS was employed. The BWCS was developed after tolerable depth of water table had been recognized (Meihana et al 2017;Lakitan et al 2018;Susilawati and Lakitan 2019;Kriswantoro et al 2020a,b). Immediately after transplanting, all pots were placed in 2m x 4m outdoor experimental pool filled with water to depth of 2 cm, for assuring water penetration into growing substrate via bottom holes of each pot.…”
Section: Plant Materials and Experimental Proceduresmentioning
confidence: 99%